The Engaged Patient: The Relevance of Patient–Physician Communication for Twenty-First-Century Health - Timmermans, Stefan (Journal of health and social behavior, 2020)
The patient–doctor interaction has changed profoundly in the past decades. In reaction to paternalistic communication patterns, health policy makers have advocated for patient-centered care and shared decision-making. Although these models of medical communication remain still aspirational, patients have become more engaged in advocating for their own health in encounters with physicians. I argue that the engaged patient is a more accurate conceptualization of the changing role of the patient than patient consumerism, the empowered, or expert patient. I examine how the emergence of engaged patients influences the autonomy of health professionals, relates to the rise of the internet as an alternative source of medical information, centers the role of the patient–doctor interaction in public health epidemics, and contributes to health inequities.